Cellular Therapeutic Approaches to Cytomegalovirus Infection Following Allogeneic Stem Cell Transplantation - Shafat, Manar S.; Mehra, Vedika; Peggs, Karl S.; Roddie, Claire (Frontiers in Immunology, 2020)
Cytomegalovirus (CMV) infection is common following allogeneic hematopoietic stem cell transplant (HSCT) and is a major cause of morbidity and increased mortality. Whilst pharmacotherapy can be effective in the prevention and treatment of CMV, these agents are often expensive, toxic and in some cases ineffective due to viral resistance mechanisms. Immunotherapeutic approaches are compelling and early clinical trials of adoptively transferred donor-derived virus-specific T (VST) cells against CMV have demonstrated efficacy. However, significant logistical challenges limit their broad application. Strategies to optimize VST manufacture and cell banking alongside scientific developments to enhance efficacy whilst minimizing toxicity are ongoing. This review will discuss the development of CMV-specific T-cell therapies, the challenges of widespread delivery of VSTs for CMV and explore how VST therapy can change outcomes in CMV infection following HSCT.